Slumber’s Duel: The Upstart Orexin Receptor Antagonists Versus the Battle-Hardened Z-Drugs: Systematic Review and Meta-Analysis Unveiling a Tale of Efficacy and Safety of Two Contenders - Asha Devi Dhandapani; Sathyan Soundara Rajan; Gaurav Uppal; Sneh Babhulkar; Betsy Marina Babu (BJPsych Open)
Aims: Primary insomnia, a separate diagnosis that is now included within the newly broader categorization of insomnia, greatly affects the quality of life. This meta-analysis evaluates the efficacy and safety of orexin receptor antagonists (ORAs) and Z-drugs for insomnia in adults.